Methodology of Writing the Book Nayl Al-Autar min Ahadith Sa'id Al-Akhyar Sharh Muntaqa Al-Akhbar by Muhammad Bin Ali Al-Shaukani - Nafsiyah, Fitrotun; Gunadi , Syahrul; Wang, Yuanyuan; Zou, Guijiao (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
The Hadith is the second guideline after the Qur'an for Muslims. The position of hadith in Islam cannot be hypothesized anymore, therefore along with the study of hadith, either the hadith books or the sharah books. There are so many hadith books that are famous among Muslims, until in the end they made new breakthroughs in creating their best work for hadith, one of which is the book of Nail al-Autar by Muhammad bin Ali al-Shaukani. This book has its own uniqueness in its sharah, which uses the method of ijmali, tahlili, muqarin and other scholarly opinions. In this study, it uses qualitative methods that are library research (library research). This book is organized based on the books of jurisprudence, and the scope of the themes contained in it is also related to jurisprudence. This book is one of the books that contains many opinions of madzhab priests such as imam Malik, imam Hanbali, imam Shafi'I and imam Hanafi